Design, Synthesis and Biological Profiling of Novel Phenothiazine Derivatives as Potent Antitubercular Agents - Sellamuthu, Satheeshkumar; Kumar, Ashok; Nath, Gopal; Singh, Sushil Kumar (Bentham Science Publishers B.V., 2018)
Background: Neuroleptic phenothiazines have been reported for antitubercular activity, but the unwanted side effect (antipsychotic activity) restricted their use as antitubercular drugs. Objective: The study aimed to carry out development of phenothiazine based antitubercular agents by modifying/removing the chemical group(s)/ linker(s) of chlorpromazine essential for exerting an antipsychotic effect. Methods: The designed molecules were filtered with a cut-off of docking score < 2.0 Kcal/mol against dopamine receptors, so that their binding with the receptor would be reduced to produce no/ less antipsychotic effect. The molecules were then synthesized and screened against M. tuberculosis H37Rv. They were further screened against a gram-positive (S. aureus) and a gram-negative (E. coli) bacterial strains to evaluate the spectrum of activity. The ability of the compounds to cross the blood-brain barrier (BBB) was also analyzed. The compounds were further examined for cytotoxicity (CC 50 ) against mammalian VERO cells. Results: Compounds 14p, 15p and 16p were found to be the most effective against all the strains viz. M. tuberculosis H37Rv, S. aureus and E. coli with MIC of 1.56µg/ml, 0.98µg/ml and 3.91µg/ml, respectively. Further, BBB permeability was found to be diminished in comparison to chlorpromazine, which would ultimately reduce the unwanted antipsychotic activity. They were also found to be free from toxicity against VERO cells. Conclusion: The designed strategy, to enhance the antitubercular activity with concomitant reduction of dopamine receptor binding and BBB permeability was proved to be fruitful.
Keywords: Antibacterial; Antitubercular; BBB permeability; Cytotoxicity; Molecular property; OSIRIS DataWarrior; Phenothiazine